Effect of chitosan on buck semen quality and semen plasma metabolites during low-temperature storage - Song, Meijun; Jia, Bingke; Dai, Dinghui; Xu, Xiaoli; Cao, Jiaxue; Guo, Jiazhong; Wang, Linjie; Zhong, Tao; Zhan, Siyuan; Li, Li; Zhang, Hongping (Frontiers in Veterinary Science, 2025)
BackgroundOptimizing buck semen preservation techniques can significantly advance the goat industry. This study aimed to investigate the effects of chitosan on sperm quality and seminal plasma metabolite profiles in bucks during low-temperature storage at 4°C.ResultsThe results showed that when 0.2 mg/mL chitosan was added to semen dilution, sperm viability and antioxidant capacity were highest and significantly higher than the control group (p < 0.05). Sperm viability decreased progressively with increasing storage time at 4°C. However, on day 5, sperm viability was significantly higher in all groups where chitosan was added to the semen dilutions than in the control group (p < 0.05). A total of 23 classes of metabolites were detected in the non-targeted metabolism group of seminal plasma. The metabolite caused by chitosan mainly included fatty acyls, phospholipids, amino acids and organic acids. Most differential metabolites in fatty acyls and glycerophospholipids in chitosan-treated semen were decreased and enriched in the anabolic pathway of unsaturated fatty acids. Additionally, several oligopeptides showed correlations with sperm quality.ConclusionThese results suggest that adding 0.2 mg/mL chitosan to semen diluent successfully prolongs the low-temperature preservation of semen mainly by altering the anabolism of lipids and amino acids. This provides theoretical support and practical reference for the applying chitosan in the low-temperature preservation of buck semen.